Use of Dairy Products in people living with diabetes - Sanjay Kalra; Saurabh Arora; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
Dairy products are a good source of protein, energy and calcium. Unfortunately, because of various misconceptions, they are often avoided by people living with diabetes. This article enumerates the wide variety of dairy products available in the South Asian cuisine, explores their nutritional characteristics, and explains how to consume them in a healthy manner. Furthermore, this manuscript also highlights the utility of dairy products in people living with diabetes and its impact on improving glycemic control. Keywords: Cheese, Curd, Dairy, Ghee, Medical Nutritional Therapy, Yoghurt